2016
DOI: 10.1152/ajpcell.00325.2015
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Bruton's tyrosine kinase inhibitors impairs GPVI-mediated platelet function

Abstract: The Tec family kinase Bruton's tyrosine kinase (Btk) plays an important signaling role downstream of immunoreceptor tyrosine-based activation motifs in hematopoietic cells. Mutations in Btk are involved in impaired B-cell maturation in X-linked agammaglobulinemia, and Btk has been investigated for its role in platelet activation via activation of the effector protein phospholipase Cγ2 downstream of the platelet membrane glycoprotein VI (GPVI). Because of its role in hematopoietic cell signaling, Btk has become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 26 publications
1
51
0
2
Order By: Relevance
“…In addition, evidence was obtained for reduced α IIb β 3 ‐dependent outside‐in signaling, linked to thrombus instability in vitro . Several studies have confirmed that Btk can act as a central target of ibrutinib in GPVI‐stimulated platelets, although downstream tyrosine kinases may be affected as well . In vitro , ibrutinib was found to fully inhibit the tyrosine phosphorylation of Src and PLCγ2 .…”
Section: Effects Of Tkis On Platelet Functionmentioning
confidence: 97%
“…In addition, evidence was obtained for reduced α IIb β 3 ‐dependent outside‐in signaling, linked to thrombus instability in vitro . Several studies have confirmed that Btk can act as a central target of ibrutinib in GPVI‐stimulated platelets, although downstream tyrosine kinases may be affected as well . In vitro , ibrutinib was found to fully inhibit the tyrosine phosphorylation of Src and PLCγ2 .…”
Section: Effects Of Tkis On Platelet Functionmentioning
confidence: 97%
“…In contrast, administration of ibrutinib analogs in non-human primates had no significant effect on bleeding time despite the ability to inhibit collagen-mediated platelet activation in vitro and ex vivo following treatment. 8 This begs the question as to whether ibrutinib alone is responsible for causing bleeding in patients. In the present study, we examined the impact of ibrutinib on platelet function in the context of inflammatory hemorrhage and primary hemostasis in mice.…”
mentioning
confidence: 99%
“…In most trials, the frequency of grade 3 or 4 bleeding events has been low at c. 3-4%. These acquired defects are consistent with an on-target inhibition of BTK signalling downstream from both the platelet collagen receptor glycoprotein (GP)VI, and the von Willebrand factor receptor, GPIb-V-IX (Quek et al, 1998;Bye et al, 2015;Rigg et al, 2016). The utility of platelet function testing for patients on ibrutinib has not been established, but platelet aggregation responses to collagen (Kamel et al, 2015;Lipsky et al, 2015) and ristocetin are primarily affected (Kazianka et al, 2015).…”
Section: Ibrutinib and Bleeding Riskmentioning
confidence: 80%